[FeFe]‐Hydrogenase: Defined Lysate‐Free Maturation Reveals a Key Role for Lipoyl‐H‐Protein in DTMA Ligand Biosynthesis. (11th April 2022) - Pagnier, Adrien; Balci, Batuhan; Shepard, Eric M.; Yang, Hao; Warui, Douglas M.; Impano, Stella; Booker, Squire J.; Hoffman, Brian M.; Broderick, William E.; Broderick, Joan B.
Abstract: Maturation of [FeFe]‐hydrogenase (HydA) involves synthesis of a CO, CN −, and dithiomethylamine (DTMA)‐coordinated 2Fe subcluster that is inserted into HydA to make the active hydrogenase. This process requires three maturation enzymes: the radical S‐adenosyl‐l ‐methionine (SAM) enzymes HydE and HydG, and the GTPase HydF. In vitro maturation with purified maturation enzymes has been possible only when clarified cell lysate was added, with the lysate presumably providing essential components for DTMA synthesis and delivery. Here we report maturation of [FeFe]‐hydrogenase using a fully defined system that includes components of the glycine cleavage system (GCS), but no cell lysate. Our results reveal for the first time an essential role for the aminomethyl‐lipoyl‐H‐protein of the GCS in hydrogenase maturation and the synthesis of the DTMA ligand of the H‐cluster. In addition, we show that ammonia is the source of the bridgehead nitrogen of DTMA. Abstract : The aminomethyl‐lipoyl‐H‐protein (Hmet ) of the glycine cleavage system (GCS) is shown to play a key role in maturation of the [FeFe]‐hydrogenase. Including Hmet, or Hmet plus other components of the GCS, allows maturation by purified HydE, HydF, and HydG in the absence of cell lysate for the first time.